Compliance With FDA Nicotine Warning Statement Provisions in E-liquid Promotion Posts on Instagram - Laestadius, Linnea I (Nicotine Tob Res, 2020)
INTRODUCTION: Effective August 2018, the U.S. Food and Drug Administration (FDA) required that nicotine addiction warnings be placed on ads for nicotine containing e-liquids. As per FDA comments, this provision pertains to visual ads communicated via social media, raising questions about compliance within the large e-liquid promotion community on Instagram. AIMS AND METHODS: This study examines use of warnings on promotional Instagram posts before and after provisions took effect on August 10, 2018. Netlytic was used to gather a sample of 500 promotional #eliquid and #ejuice posts from: May 2017, October 2017, March 2018, August 2018, and September 2018. The 1500 prewarning and 1000 postwarning posts were coded using content analysis. Changes in products and marketing strategies were also considered. Post volume was tracked monthly between May 2017 and February 2020. RESULTS: In the prewarning period, nicotine warning statements were absent on all posts. Following August 10, 2018, FDA compliant warnings were present on 13.6% of posts. Among US-based posts, 36.4% used the warnings, with warnings more common on posts made by e-liquid brands (52.3%) and posts promoting e-liquids with nicotine (40.0%). Promotional strategies and products did not significantly change. The share of posts made by US Instagram users decreased by 11%, although total post volume continued to grow. CONCLUSIONS: Many e-liquid promotion posts on Instagram remained noncompliant with nicotine warnings after FDA provisions took effect. The large volume of international users also limited the impact of FDA-mandated warnings on the social media environment. IMPLICATIONS: Further guidance and enforcement are needed to ensure that US e-liquid marketers on visual social media platforms adhere to current provisions, particularly for individual social media users who are sponsored by industry. The inherently global span of social media also indicates the importance of a shared approach to marketing regulations. Further work is needed to assess enforcement strategies viable for the social media environment.